KEBIJAKAN PEMERINTAH INDONESIA MENETAPKAN HARGA PATOKAN EKSPOR PRODUK KAKAO DARI INDONESIA KE TIONGKOK TAHUN 2012-2015 - Dicky Shandri; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describe the policy of Government of Indonesia implemented export constant price for cocoa product from Indonesia to China in 2012-2015. Indonesia are one of most countries that have production of cocoa between Pantai Gading, Ghana and Brazilia. China are one of country that be a export purpose cocoa product from Indonesia. But in 2010 China have create a protection policy with increase the tax for cocoa export from Indonesia and it’s make disadvantage for Indonesia.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the policy of Government of Indonesia implemented export constant price for cocoa product from Indonesia to China. The theories applied in this research are merchantilism with the foreign policy theory from Viotti Kaupi.The result shows that the policy of Government of Indonesia implemented export constant price for cocoa product from Indonesia to China are becaused trade protection from China with implemented custom tariff 10% for cocoa product from Indonesia and 0% for the other countries likes Malaysia, Thailand and etc. The policy of Government of Indonesia implemented export constant price for cocoa product from Indonesia to China are by Trade minister regulations Number 21/M/DAG/PER/5/2010 about constant price for ex customin standart proce for cocoa products.Key words: policy, constant, price and cocoa